Greece : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper explores the determinants of Greece's potential output, an exercise that could shed light on its current cyclical position, as well as on its medium-term growth prospects. To that end, a production function is estimated, with capital and labor as factors of production and time-varying total factor productivity. The estimation results suggest that the output gap has been closing in recent years, with output projected to be slightly above potential in 1998. The paper also explores the impact of changes in the drachma's exchange rate on inflation.